Undiagnosed intracranial lipoma associated with sudden death - Carlos Durão; Frederico Pedrosa (Elsevier, 2017)
Intracranial lipomas represent less than 0.1% of all intracranial tumors. They are usually located in the callus area and often asymptomatic. This paper presents a sudden death case after an episode of convulsions on a 39 years old woman with a history of migraines and seizures since adolescence. The autopsy revealed the presence of an undiagnosed massive brain lipoma (60 × 35 mm) associated with atrophy of the corpus callosum. Although very rare and seldom malignant these may be associated with seizures and sudden death. Keywords: Intracranial lipoma, Brain lipoma, Sudden death